Integrated Reporting and the Yin-Yang Perspective: Towards Moral and Sustainable Value Creation - Astrid Maharani; Agung Parmono (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This article investigates the transformation of corporate disclosure through Integrated Reporting (IR) and examines it within the Yin-Yang philosophical framework. The study departs from the growing demand for transparent, reliable, and sustainable reporting that integrates financial and non-financial information to create long-term value for stakeholders. Despite Indonesia’s role as a G20 member, the adoption of IR remains limited and often incomplete, which raises questions about its effectiveness in promoting sustainable practices. Positioning the research within the context of moral and sustainable perspectives, this study argues that the Yin-Yang philosophy offers a valuable lens for understanding the ethical balance required in corporate reporting. The analysis employs a qualitative literature-based method by reviewing IR principles in relation to Yin-Yang values of balance, complementarity, and dynamism. The findings indicate that Yin-Yang provides a framework to harmonise financial accountability with social and environmental responsibility, thereby encouraging sustainable value creation. This study contributes conceptually by linking Eastern philosophy with IR discourse and practically by highlighting the need for Indonesian companies to enhance IR implementation. The article underscores that adopting a balanced, moral, and sustainable approach to corporate reporting can strengthen stakeholder trust and support long-term business resilience.